ARIMA forecasting of China's coal consumption, price and investment by 2030. Issue 3 (4th March 2018) - Jiang, Shumin; Yang, Chen; Guo, Jingtao; Ding, Zhanwen
ABSTRACT: Forecasting of energy consumption, price, and investment in coal industry is one of the most important proactive approaches and policy instruments used by decision-makers in China. Due to the richer information on time-related changes than the other methods, autoregressive integrated moving average (ARIMA) is applied to estimate the further coal price, consumption, and investment of China from 2016 to 2030. The best-fitted models for coal price, consumption, and investment at each predicted step are selected. The empirical results show that the annual average rate of coal consumption and investment will decrease between 2016 and 2030 except for coal price, which exhibits fluctuant behavior in the forecast period. The annual droop rate of coal consumption from 2016 to 2030 will be rather big, nearly the same with the annual growth rate from 2000 to 2015. The coal investment has the similar result with coal consumption.